Immunophenotyping of pulmonary sarcomatoid carcinoma - Ma, Yu; Li, Wensheng; Li, Zhenzhen; Chen, Jie; Wang, Hongtao; Jiang, Tao; Zhu, Jianfei (Frontiers in Immunology, 2022)
Background Previous studies have suggested that patients with pulmonary sarcomatoid carcinoma (PSC)may benefit from immune checkpoint inhibitors (ICIs); however, relevant data are lacking. This study aimed to establish the immunophenotype of PSC by assessing PD-L1 and CD8+ T-cell infiltration. Methods A retrospective analysis of pathologically confirmed PSC cases from two centers was performed from January 2009 to May 2021. According to the infiltration of CD8+ T cells in different spatial regions, patients were classified into three types: immune-inflamed, immune-excluded, and immune desert. PD-L1 staining was also performed on the intratumoral region and the tumor proportion score (TPS) was used for scoring. Combined with CD8+ T-cell infiltration and PD-L1 expression in the intratumoral region, immunophenotyping can be divided into four types: type I (PD-L1+/CD8+, adaptive immune resistance), type II (PD-L1-/CD8-, immunologic ignorance), type III (PD-L1+/CD8-, intrinsic induction), and type IV (PD-L1-/CD8+, tolerance). Finally, correlation analysis was performed on the immunophenotype, clinicopathological characteristics, and outcomes of the patients. Results A total of 32 patients with PSC were included in the final analysis. Of these patients, 65.6% (21/32), 15.6% (5/32), and 18.8% (6/32) were classified as immune-inflamed, immune-excluded, and immune-desert, respectively. Notably, the immune-inflamed type is predominantly observed in pleomorphic carcinomas (PC, 66.7%). Moreover, among these participants, 19 (59.4%) were classified as PD-L1 positive according to the TPS score. In particular, 11 (34.4%) patients had PD-L1 TPS scores >50%. Next, we immunophenotyped patients with PSC based on CD8+ T cell infiltration and tumor cell PD-L1 expression (types I–IV). Type I (PD-L1+/CD8+, adaptive immune resistance) was the most prevalent subtype, accounting for 46.9% (15/32), followed by type II (PD-L1-/CD8-, immunological ignorance) (21.9%), type IV (PD-L1-/CD8+, tolerance) (18.7%), and type III (PD-L1+/CD8-, intrinsic induction) (12.5%). Finally, we performed a survival analysis and found that neither immunophenotype was a predictor of prognosis in patients with PSC. Multivariate analysis showed that pneumonectomy increased the risk of death by four times compared with lobectomy (RR: 4.1; 95% CI:1.3-12.4, P=0.014). Conclusion Patients with PSC are characterized by immune-inflamed type and type I (PD-L1+/CD8+, adaptive immune resistance), explaining the intrinsic reasons for their high response rate to immunotherapy.